Learning Opportunities in Peer Interaction and the Influence of the Social Context - Leslie, Carolyn E. (Linguarum Arena, 2017)
This study investigated peer oral interaction in two adult task based language teaching classrooms, both at B1 level, ffocusing on how learners created learning opportunities during peer interaction and the way in which the social context shaped the provision of these opportunities. The study was carried out over the period of one academic year with research being conducted in the classrooms as part of regular class work. The research was framed within a sociocognitive perspective of second language learning and the data presented here comes from audio-recorded talk of dyads, triads and groups of four students completing oral tasks. These audio recordings were transcribed and analysed qualitatively using conversation analysis for interactions that led to learning opportunities and those which encouraged a positive social dimension. Transcriptions were also analysed quantitatively for language leading to learning opportunities. Analysis of interactions revealed the many ways in which learners in both groups created learning opportunities. Results showed that the social context influences the number of learning opportunities created, and it is often the nature of the relationship between the individual members of the small groups completing the tasks, which influences the effectiveness of oral interaction for learning. This study contributes to our understanding of the way in which learners individualise the learning space and highlights the situated nature of language learning. It shows how individuals interact with each other and how talk in interaction changes moment-by-moment as learners react to the here and now of the classroom environment.